Character Educatıon Framework For Multıracıal Socıety In Malaysıa - Sakinah, S., Alwi, M.Y., Mohd Aderi Che Noh (International Journal of Advanced Science and Technology, 2020)
This concept paper is about character education framework within the context of multira-cial society in Malaysia. It discussed social development from the perspective of integrat-ed education. In the context of multiracial and multicultural society, character education is needed to address the issue of education from different social settings. As such, within the Malaysian context it is Malay, Chinese and Indian education blended together to de-velop social cohesive society in Malaysia. The unique aspect of multiracial and multiethnic society in Malaysia where each society inherited its own educational legacy is now bridged by a cohesive character education framework that makes a real Malaysian society though bound by racial element but united through cohesive values. Integrating universal values, and cultures that bind together different ethnics using common language, and ap-proach is an integral part of character education framework.